Utilizing Digital Storytelling and Social Media to Expand The Reach of Tourism Village Promotion: Pengabdian - Firlie Lanovia Amir; Firman Sinaga; Febianti; Komang Trigita Juliastari; Komang Shanty Muni Parwati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Sektor pariwisata berbasis desa (desa wisata) di Bali memiliki potensi budaya dan alam yang luar biasa, namun serin The village-based tourism sector (tourist villages) in Bali has extraordinary cultural and natural potential, but often faces obstacles in the effectiveness of promotion and market reach. This Community Service (PkM) aims to increase the capacity of tourism village managers in expanding promotional reach through the use of Digital Storytelling and social media. The use of digital narrative methods is considered to provide a stronger emotional value for potential tourists compared to conventional promotions. Partners in this activity are tourism awareness groups (Pokdarwis) and tourism village managers in Bali. The implementation method of the activity includes three main stages: (1) training in creating storytelling-based content, (2) technical assistance in optimizing social media (such as Instagram, TikTok, and YouTube), and (3) evaluation and monitoring of content sustainability. The results of this PkM activity show an 85% increase in partners' understanding in creating engaging digital narratives, as well as an increase in interaction (engagement rate) on tourism village social media after the program implementation. Through this activity, partner tourism villages are now able to independently produce authentic and creative promotional content, which in turn contributes to expanding market reach and increasing tourist visits. gkali menghadapi kendala dalam efektivitas promosi dan jangkauan pasar. Kegiatan Pengabdian Masyarakat (PkM) ini bertujuan untuk meningkatkan kapasitas pengelola desa wisata dalam memperluas jangkauan promosi melalui penggunaan Digital Storytelling dan media sosial. Penggunaan metode narasi digital dianggap memberikan nilai emosional yang lebih kuat bagi calon wisatawan dibandingkan dengan promosi konvensional. Mitra dalam kegiatan ini adalah kelompok penyadar pariwisata (Pokdarwis) dan pengelola desa wisata di Bali. Metode pelaksanaan kegiatan ini meliputi tiga tahap utama: (1) pelatihan dalam membuat konten berbasis storytelling, (2) bantuan teknis dalam mengoptimalkan media sosial (seperti Instagram, TikTok, dan YouTube), dan (3) evaluasi dan pemantauan keberlanjutan konten. Hasil kegiatan PkM ini menunjukkan peningkatan pemahaman mitra sebesar 85% dalam menciptakan narasi digital yang menarik, serta peningkatan interaksi (tingkat keterlibatan) di media sosial desa wisata setelah pelaksanaan program. Melalui kegiatan ini, desa-desa wisata mitra kini mampu secara mandiri memproduksi konten promosi yang autentik dan kreatif, yang pada gilirannya berkontribusi pada perluasan jangkauan pasar dan peningkatan kunjungan wisatawan.